2011
DOI: 10.1186/1471-244x-11-198
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in depressive and anxiety symptoms among primary care patients and in patients with depressive and anxiety disorders; results from the Netherlands Study of Depression and Anxiety

Abstract: BackgroundLittle is known about seasonality of specific depressive symptoms and anxiety symptoms in different patient populations. This study aims to assess seasonal variation of depressive and anxiety symptoms in a primary care population and across participants who were classified in diagnostic groups 1) healthy controls 2) patients with a major depressive disorder, 3) patients with any anxiety disorder and 4) patients with a major depression and any anxiety disorder.MethodsData were used from the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
4
40
0
1
Order By: Relevance
“…Recent reports have found seasonal changes in occurrence of anxiety and depression [6] and seasonality of key neurotransmitters involved in mood has been documented [21,22]. Our analysis showed a strong winter and early spring increase in obsessive-compulsive disorder (300.3), dysthymic disorder (300.4), shown in Figure 3A, and other depressive disorders (311).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Recent reports have found seasonal changes in occurrence of anxiety and depression [6] and seasonality of key neurotransmitters involved in mood has been documented [21,22]. Our analysis showed a strong winter and early spring increase in obsessive-compulsive disorder (300.3), dysthymic disorder (300.4), shown in Figure 3A, and other depressive disorders (311).…”
Section: Resultssupporting
confidence: 61%
“…These breakthrough findings have suggested that the thus far unidentified causative pathogen may be a windborne microbe. Other groups have sought to confirm anecdotal findings of seasonal or climate related changes in disease rates, including heart failure [5], depression and anxiety [6], varicose vein ulcers [7], urinary tract infection [8,9], and even cancer [10]. While some of these works searched for seasonality using purpose-driven surveys, Upshur [11] used coded administrative data derived from a large EHR system to investigate whether seasonal peaks in incidence were a common feature in a limited set of the most frequent diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus irrespective of the definition there is evidence of seasonal variation in CES-D scores suggesting that those interviewed in the colder, darker months had greater levels of depressive symptoms. However, in common with the earlier report from the Netherlands Study of Depression and Anxiety group investigating seasonality in objective depressive symptoms (Winthorst et al, 2011), although we saw statistical trends towards seasonal variation using either definition the absolute effect on depressive symptoms is small ( o1 on the CES-D). In addition, we note that our collection period covers two winters and one of each of the other seasons -however similar numbers of participants were interviewed in winter months and summer months.…”
Section: Discussionsupporting
confidence: 50%
“…Unfortunately, this study does not assess SAD itself, but the higher and lower prevalence of complaints of depression in a cross-sectional approach. In a cross-sectional cohort study, using the Kessler Psychological Distress Scale (K10), Winthorst et al142 did not find a clear seasonal pattern in predefined depressive subgroups. Using the SPAQ in the same population, some seasonal variation was found in subgroups with depression and anxiety 143.…”
Section: Criticismsmentioning
confidence: 99%